2006
DOI: 10.2215/cjn.00630805
|View full text |Cite
|
Sign up to set email alerts
|

Role of Socioeconomic Status in Kidney Transplant Outcome

Abstract: There is controversy regarding the influence of genetic versus environmental factors on kidney transplant outcome in minority groups. The goal of this project was to evaluate the role of certain socioeconomic factors in allograft and recipient survival. Graft and recipient survival data from the United States Renal Data System were analyzed using Cox modeling with primary variables of interest, including recipient education level, citizenship, and primary source of pay for medical service. College (hazard rati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
107
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 123 publications
(124 citation statements)
references
References 32 publications
(33 reference statements)
9
107
1
Order By: Relevance
“…The role of socioeconomic status (SES) in determining access to transplantation services is complex because SES affects care throughout the transplant process (8,9). Patients with low SES often delay seeking medical care and lack access to specialty services, leading to delays in transplant referral, evaluation, and listing (10,11).…”
mentioning
confidence: 99%
“…The role of socioeconomic status (SES) in determining access to transplantation services is complex because SES affects care throughout the transplant process (8,9). Patients with low SES often delay seeking medical care and lack access to specialty services, leading to delays in transplant referral, evaluation, and listing (10,11).…”
mentioning
confidence: 99%
“…In the United States, educational level has been shown to be a determinant of access to and outcome after kidney transplantation. 32,33 However, these disparities in access to transplant do not apply to our population, in which all the studied patients were already under evaluation for liver transplantation at the same center. Taking into account the data for 14,814 recipients of liver transplants from 1987 to 2001 in the United Network for Organ Sharing database, researchers found that education had only a marginal influence on the outcome; survival was lower in those with only a highschool education versus those who had graduated from college.…”
Section: Discussionmentioning
confidence: 91%
“…These characteristics are distributed unequally in the racial groups 28 and they found to be associated with the clinical outcome (e.g. employment status, 29 health insurance type, 30 education level, 30 marital status, 31 substance abuse 32 ), may affect the outcome of kidney transplantation.…”
Section: Existing Disparities In Kidney Transplantationmentioning
confidence: 99%
“…30 Similar to the access to transplantation, the degree of disparities in graft and recipient survival between African Americans and whites gradually decreased with increasing level of education.…”
Section: Transplant Outcomementioning
confidence: 99%
See 1 more Smart Citation